Descriptive sensory analysis of Pampanga-sourced Philippine Sweet Bacon (PSB) - Faylona, Aaron C.
The study aimed to describe the sensory characteristics of Pampanga-sourced Philippine Sweet Bacon (PSB). A preliminary market survey was done amongst kapampangans to determine the most prevalent and consumed PSB brands [i.e., Pampanga’s Best (PB), Roel’s (RL), and Mekeni (MK) tocino] among kapampangans (n = 50). A standardized training method for descriptive analysis of PSB was developed. The PSB variants were then subjected to General Descriptive Analysis by a set of trained panelists (n = 6) using 150-pt line scale based on the developed standardized protocol. The study results reveal that there are no significant differences (p < 0.05) between the sensory characteristics of Pampanga-sourced PSB across different brands. Sensory scores ranged from 27.61-34.56 for sweet aroma, 64.72-74.44 for fatty aroma, 56.39-74.56 for smokey aroma, 56.39-64.44 for fatty flavor, 46.05-53.89 for meaty flavor, 33.06-40.00 for smokey flavor, 88.06-94.44 for sweet taste, 7.59-10.41 for sour taste, and 78.33-95 for salty taste. The results of this research represent a first attempt to obtain baseline data towards the standardization of PSB, with particular focus on its descriptive sensory characteristics. The research results and methodologies may be used by PSB producers, the government, as well as other stakeholders to understand the descriptive profile of PSB and build upon them towards standardization and product development of the food commodity.